1:10000 scale mapping with GPS and free GIS tools – comparison with topographic map - Andor Rábay (Acta Geographica Debrecina. Landscape & Environment Series)
Reliability of the road system illustrated on topographic maps with 1:10000 scale is questionable due to their age, but surveying a territory with area over 100 hectares is expensive with classical geodetic tools, although there is no need of geodetic accuracy in most cases. GPS-based mapping method described in this paper is suitable in these situations. The main concept is to keep the costs of the survey as low as possible, therefore free GIS applications and databases were used with navigation purpose GPS receivers. The accuracy provided by these devices is good enough for those purposes where the accuracy of topographic map with 1:10000 scale is adequate. GPS-based mapping can be done to update the road system of existing map or create own detailed road databases. The result of the work is not just a database but a navigation capable digital map, which can aid further activities on the field, like geographic researches, environment protection, tourism, fire service etc.